Subchronic exposure to arsenic induces apoptosis in the hippocampus of the mouse brains through the Bcl‐2/Bax pathway. Issue 3 (14th July 2015) - Wang, Yachen; Bai, Canming; Guan, Huai; Chen, Ruolin; Wang, Xiaoxu; Wang, Bingwen; Jin, Hetian; Piao, Fengyuan
Abstract : Subchronic exposure to arsenic induces apoptosis in the hippocampus of the mouse brains through the Bcl‐2/Bax pathway: Yachen Wang, et al . Department of Occupational and Environmental Health, Dalian Medical University, P.R. China Objective: The aim of this study was to identify whether arsenic (As) exposure could induce hippocampal neural apoptosis in vivo. Methods: Sixty‐four mice were randomly divided into 4 groups of 16 each. Group 1 orally received drinking water alone as a control. Groups 2−4 were given arsenic trioxide (As2 O3 ) orally at the doses of 1 ppm, 2 ppm and 4 ppm, respectively. All the treatments continued for 60 days. Morphological changes in the hippocampus were observed by HE staining. Apoptosis in the hippocampus was examined by TUNEL assay and transmission electron microscopy. The expression levels of Bcl‐2 and Bax genes and their proteins in the hippocampus were determined by realtime PCR and Western blotting. The activity of caspase‐3 was determined by spectrophotometry. Results: Abnormal histopathological changes and apoptosis were found in the hippocampus of As‐exposed mice. The expressions of the Bcl‐2 gene and its protein in the hippocampus of As‐exposed mice were significantly lower than those in the control group ( p <0.05). However, the expressions of the Bax gene and its protein, and the expression ratio of Bax/Bcl‐2 in the hippocampus were significantly higher in the groups exposed to As than in the control group ( p <0.05). Moreover, the activity of caspase‐3 in the hippocampus of mice exposed to As was higher than that in the control ( p <0.05). Conclusions: These results indicate that subchronic exposure to As induces apoptosis in the hippocampus of mice by disturbing normal Bax/Bcl‐2 regulatory pathways. Meanwhile, it is suggested that the induced apoptosis in the hippocampus may be at least partly responsible for As‐induced neurotoxicity.